The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1583/07-2182.1
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Abdominal Aortic Aneurysm Repair With a Preferential Endovascular Strategy:Mortality and Cost-Effectiveness Analysis

Abstract: A preferential eEVAR protocol for acute AAA can decrease mortality and does not increase overall costs during initial treatment, but larger studies are needed to determine if these trends are statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…4 In our own report designed to define cost-effectiveness of the introduction of a preferential endovascular strategy in patients with AAAA, we found that in-hospital mortality dropped from 31% (historical open repair control group) to 18% (for endovascular repair of selected patients). 5 These results compare well with the literature and resulted in a local treatment strategy in which patients were virtually never denied treatment, regardless of their age.…”
supporting
confidence: 82%
“…4 In our own report designed to define cost-effectiveness of the introduction of a preferential endovascular strategy in patients with AAAA, we found that in-hospital mortality dropped from 31% (historical open repair control group) to 18% (for endovascular repair of selected patients). 5 These results compare well with the literature and resulted in a local treatment strategy in which patients were virtually never denied treatment, regardless of their age.…”
supporting
confidence: 82%
“…56 The cost savings obtained from decreased morbidity, mortality, and decreased LOS at the initial time of surgery is offset by the cost of the device, continued surveillance, and increased reintervention rates compared to open repair. [21][22][23][24] However, when it comes to traumatic aortic injuries, the difference in perioperative morbidity and mortality is larger compared with differences seen for EV for AAAs. Therefore, the cost savings is also significantly higher, especially when we factor in the cost associated with treating a patient who develops paraplegia, which can cost over $100,000 in the first year alone.…”
Section: Discussionmentioning
confidence: 99%
“…15,20 Although EV of AAAs has inconsistently shown to be cost effective, the mortality, morbidity (paraplegia rate) and LOS benefits are significantly greater for patients with BTAI than for elective aneurysm repair. 15,[21][22][23][24] Therefore, we postulate that the cost savings from EV repair of BTAIs would outweigh the cost of the device, surveillance, and reinterventions. Currently, there are no studies that have evaluated the cost effectiveness of EV in the setting of thoracic aortic injury.…”
mentioning
confidence: 99%
“…A prospective cohort study by Kapma et al [54] utilising a preferential protocol favouring EVAR was compared to a historical group of patients treated with OR. It was found that treatment with EVAR was not more expensive than OR, however, the conclusions drawn are limited by the study design and small sample size [54].…”
Section: Research Articlementioning
confidence: 99%